321 S-ADENOSYLMETHIONINE AMELIORATES ETHANOL-INDUCED OXIDATIVE DAMAGE IN THE MURINE DEVELOPING BRAIN. (10th December 2015) - Ciener, D.; Wang, X. P.; Wen, T. C.; Genetta, T.; Rogido, M.
Abstract : Background: Fetal alcohol exposure (FAE) remains the leading preventable cause for mental retardation. Although the precise mechanisms underlying the deleterious effects of alcohol remain unclear, oxidative stress, including lipid peroxidation and DNA damage have been implicated. It has previously been shown that administration of S-adenosylmethionine (SAM), a GSH precursor, can mitigate alcohol-induced oxidative damage in the liver and other tissues. In our preliminary data, SAM also restored normal head circumference in FAE guinea pig pups. Purpose: To determine the effect of SAM on alcohol-induced oxidative damage in the developing brain. Methods: Pregnant C57 female mice were given a liquid diet containing ethanol to provide 20% of calories (ETOH group; n = 5). Treatment group received same liquid diet + SAM (400 mg/kg) added to the diet during the entire pregnancy (SAM group; n = 4). Control group (n = 5) received regular rodent diet. At birth pups were sacrificed, brains removed, fixed and cryosectioned. Oxidative stress was assessed by immunohistochemical methods using monoclonal antibodies against 8-hydroxy-2′-deoxyguanosine (8OHdG), an oxidative DNA product, and 4-hydroxy-2-nonenal (HNE), a lipid peroxidation product. Results: Neural cells showed very weak and patchy 8OHdG and HNE immunoreactivity in cortex, hippocampus and ventricular zone (VZ) in control pups. Pups born after FAE showed markedly increased immunoreactivity, especially in cortical and VZ regions. The intensity and density of 8OHdG immunoreactivity were significantly ameliorated (45%) in the SAM-treated pups in both regions. Similarly, strong immunolabeling was observed in cytoplasm of neural cells in the ETOH group as evidence of HNE adducts. Immunolabeling for HNE significantly decreased (40%) in the SAM group in cortex and VZ. Conclusion: These preliminary results suggest that FAE causes significant lipid peroxidation and DNA damage to the developing mouse brain. Co-administration of SAM appears to significantly reduce the appearance of two molecular markers of oxidative stress and may be useful in protecting the developing brain exposed to alcohol in utero.